Il cortometraggio come luogo d’esibizione di un dispositivo ibrido: ragionando su Un minutito e Denise - Ugenti, Elio (Scenari, 2021)
More and more young directors use the short movie nowadays to provide the spectator with a reflection on the actual role of the cinema, also in relation to the contemporary visual and media culture. Un Minutito by Javier Macipe and Denise by Rossella Inglese, the movies taken into consideration in this article, perfectly fit into this description. The first one puts a strain on the classical distinction between fiction and documentary film through working on the style, generating a short circuit between these two expressive forms. The second one, instead, brings into its visual and narrative structure elements that stimulate crucial questions about the surveillance strategies and the use of social media. The work of some renowned scholars (i.e. Gaudreault, Eugeni, Kember and Zylinska) will provide the kick-off to reflect on some important questions: who is watching? And what is she/he looking at? And what is the role of who is being watched in these movies?